1996
DOI: 10.1177/089686089601601s41
|View full text |Cite
|
Sign up to set email alerts
|

Peritoneal Dialysis in Liver Disorders

Abstract: The purpose of this paper is to review the specific role of peritoneal dialysis (PD) in patients with liver disorders. We will pay attention to the confluence of liver diseases and situations for which chronic dialysis treatment is required. Hemodialysis (HD) and peritoneal membranes are safe barriers against the passage of the hepatitis C virus; consequently, while peritoneal effluent or HD ultrafiltrate drained from hepatitis S patients/carriers is infective, that from hepatitis C patients does not appear t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 20 publications
0
25
0
Order By: Relevance
“…The treatment for cirrhotic patients with chronic kidney disease stage 5 who required dialysis (CKD 5D) is complicated by the decreased effective intravascular volume and the subsequential hemodynamic instability. 1 , 2 Hemodialysis (HD) associated hypotension is a common complication 3 and is associated with higher mortality in patients with CKD 5 who require dialysis. 4 Multiple techniques are currently available to prevent hypotension during HD including thermal balance, 5 biofeedback systems, 6 and midodrine.…”
Section: Introductionmentioning
confidence: 99%
“…The treatment for cirrhotic patients with chronic kidney disease stage 5 who required dialysis (CKD 5D) is complicated by the decreased effective intravascular volume and the subsequential hemodynamic instability. 1 , 2 Hemodialysis (HD) associated hypotension is a common complication 3 and is associated with higher mortality in patients with CKD 5 who require dialysis. 4 Multiple techniques are currently available to prevent hypotension during HD including thermal balance, 5 biofeedback systems, 6 and midodrine.…”
Section: Introductionmentioning
confidence: 99%
“…The intestinal mucosa barrier is impaired and bacterial translocation occurs in experimental uremia [ 15 ]. Translocation of bowel flora is a cause of gram negative peritonitis in peritoneal dialysis (PD) patients [ 16 ]. A number of previous studies showed that LPS is detectable in the serum of many dialysis patients, and serum LPS level correlates with the severity of systemic inflammation and features of atherosclerosis [ 17 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hemodialysis in patients with chronic liver disease and ascites, who require dialysis for chronic renal failure, might be further complicated by intradialytic hypotension. In particular, in patients with diabetic neuropathy such as ours, limiting the amount of ultrafiltration results in residual (10). CAPD could be the treatment of choice for cirrhotic patients, particularly in cases caused by hepatitis C virus infection, with ascetic patients who require chronic dialysis (10).…”
Section: Discussionmentioning
confidence: 99%